Penerapan Teori Technology Readiness dan Technology Acceptance Model Terhadap Pengunaan Sistem Empoyee Self Service - Rakhmayani, Meita Devi; Dwianto, Agung Surya (DPPM Universitas Pelita Bangsa, 2024)
This research discusses the influence of Technology Readiness Theory (TRI) and Technology Acceptance Model (TAM) on the use of the Employee Self Service System (ESS) at PT. XYZ, a multinational company that is undergoing digital transformation. Using a descriptive quantitative approach and a post positivism paradigm, data analysis reveals that factors such as technology readiness, perceived usefulness, and ease of use contribute to employees' intention to adopt and use ESS. The implications of these findings highlight the important role of technology in improving employee efficiency and performance in the context of human resource management (HRM) in the digital era, although this research has limitations in the generalization of the findings due to its focus on one company in a particular industry.